2020
DOI: 10.3390/membranes10120397
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Bioreactor Technology: The Effect of Membrane Filtration on Biogas Potential of the Excess Sludge

Abstract: Although the membrane bioreactor technology is gaining increasing interest because of high efficiency of wastewater treatment and reuse, data on the anaerobic transformations of retentate are scarce and divergent. The effects of transmembrane pressure (TMP) in microfiltration (MF) and ultrafiltration (UF) on the pollutant rejection, susceptibility of ceramic membrane to fouling, hydraulic parameters of membrane module, and biogas productivity of retentate were determined. Irrespective of the membrane cut-off a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…The reasons for this phenomenon may be that compressible organic aggregates (such as colloids and particles) in digestate accumulated on the membrane surface or penetrate into membrane pores under the higher TMP, resulting in serious membrane fouling. Magdalena et al [ 30 ] found that an increase in TMP caused an increase in the total hydraulic resistance of membrane, resulting in more solid pollutants accumulating on the membrane surface and blocking the pores. Concentration polarization was also assumed to have an effect on the UF separation process, as the digestate contained a large amount of salts (EC = 7.7 ± 0.05 ms cm −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for this phenomenon may be that compressible organic aggregates (such as colloids and particles) in digestate accumulated on the membrane surface or penetrate into membrane pores under the higher TMP, resulting in serious membrane fouling. Magdalena et al [ 30 ] found that an increase in TMP caused an increase in the total hydraulic resistance of membrane, resulting in more solid pollutants accumulating on the membrane surface and blocking the pores. Concentration polarization was also assumed to have an effect on the UF separation process, as the digestate contained a large amount of salts (EC = 7.7 ± 0.05 ms cm −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Size exclusion is the major mechanism of rejection in UF, and the removal efficiency of UF on impurity in digestate may be impacted by its chemical speciation and distribution [ 30 ]. Table 2 shows the changes of physicochemical characteristics of the influent, concentrates, and permeates.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, UF membranes allow us to eliminate the inhibitory effects of the product and improve the process yield [10]. Conducting a comprehensive literature review (Table A1) indicated that UF membranes are extensively being used in MBRs applied for biological conversions to produce many valuable products, such as lactic acid [15][16][17][18][19][20][21][22], biohydrogen [23][24][25][26][27], biogas [28][29][30], fructose and gluconic acid [31][32][33], propionic acid [34][35][36], ethanol [37,38], succinic acid [39,40], butyric acid [41] and 1,3-propanediol (1,3-PD) [42]. The latter has received increasing attention since it is particularly attractive to industry.…”
Section: Introductionmentioning
confidence: 99%
“…It allows dissolution of weakly acidic organic matter, and consequently leads to cleavage of polysaccharides and proteins into sugars and amides, respectively [79]. Importantly, summarizing the literature data (Table A1) it can be indicated that NaOH has been used to clean both polymeric [25,41] and ceramic [28,42] UF membranes applied in MBR technology. Our previous investigations [84,85] highlighted the efficiency of NaOH solutions in removing foulants from ceramic UF membranes after filtration of glycerol postfermentation solutions containing 1,3-propanediol as a main product.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome those disadvantages and problems, there is an efficient option, biological treatment, the most used method in practice over the world because of its simplicity and low cost [7,8]. Compared with traditional biological methods (including activated sludge and the sequencing batch reactor), the submerged membrane bioreactor (SMBR) has great potential as a most promising biological treatment technology [9][10][11][12]. Nevertheless, the previous research has demonstrated that the conventional aerobic MBR is not considered a saving and feasible alternative owing to the low biodegradability of reactive soluble dyes [13,14].…”
Section: Introductionmentioning
confidence: 99%